Myeloid-Derived Suppressor Cells as a Potential Biomarker and Therapeutic Target in COVID-19 - Rowlands, Marianna; Segal, Florencia; Hartl, Dominik (Frontiers in Immunology, 2021)
Clinical presentations of COVID-19 are highly variable, yet the precise mechanisms that govern the pathophysiology of different disease courses remain poorly defined. Across the spectrum of disease severity, COVID-19 impairs both innate and adaptive host immune responses by activating innate immune cell recruitment, whilst resulting in low lymphocyte counts. Recently, several reports have shown that patients with severe COVID-19 exhibit a dysregulated myeloid cell compartment, with increased myeloid-derived suppressor cells (MDSCs) correlating with disease severity. MDSCs, in turn, promote virus survival by suppressing T-cell responses and driving a highly pro-inflammatory state through the secretion of secretion of various mediators of immune activation. Here, we summarize the evidence on MDSCs and myeloid cell dysregulation in COVID-19 infection and discuss the potential of MDSCs as biomarkers and therapeutic targets in COVID-19 pneumonia and associated disease.